Modern Aspects of Personalized Biliary Drainage in Malignant Obstructive Jaundice - Tukhtabaevich, Khuzhabaev Safarboy; Sa'dullaevich, Urozov Nu'monjon (Journal of Neonatal Surgery, 2025)
Malignant obstructive jaundice caused by tumors of the hepatopancreatoduodenal region represents a significant clinical challenge and necessitates timely biliary decompression. This study substantiates a differentiated approach to the use of minimally invasive drainage techniques (endoscopic and percutaneous) in 120 patients with inoperable tumors. It has been demonstrated that the individualized selection of drainage methods based on the level of obstruction leads to higher effectiveness, reduced complication rates, decreased need for repeated interventions, and improved survival outcomes compared to standard, uniform strategies